2011
DOI: 10.3390/molecules16032507
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Natural Organic Volatiles from Prunus mahaleb L. Honey: Coumarin and Vomifoliol as Nonspecific Biomarkers

Abstract: Headspace solid-phase microextraction (HS-SPME; PDMS/DVB fibre) and ultrasonic solvent extraction (USE; solvent A: pentane and diethyl ether (1:2 v/v), solvent B: dichloromethane) followed by gas chromatography and mass spectrometry (GC, GC-MS) were used for the analysis of Prunus mahaleb L. honey samples. Screening was focused toward chemical composition of natural organic volatiles to determine if it is useful as a method of determining honey-sourcing. A total of 34 compounds were identified in the headspace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…These results were in agreement with the studies conducted by Jerkovic et al [11] and Lusic et al [34] which found hexadecanoic acid in the unifloral honeys of black locust (Robinia pseudoacacia L.), chestnut (C. sativa L.) and fir honeydew honey (Abies alba), respectively. Hexadecanoic acid has been reported in apple blossom (M. domestica) as well as in Mahaleb cherry (Prunus mahaleb), thus revealing similarity of both volatile profiles [23,40]. Stearic acid has been reported in Malaysian Tualang honeys (Koompassia excelsa)) by Syazana et al [41].…”
Section: Honey Markers For the Characterization Of Different Unifloramentioning
confidence: 98%
“…These results were in agreement with the studies conducted by Jerkovic et al [11] and Lusic et al [34] which found hexadecanoic acid in the unifloral honeys of black locust (Robinia pseudoacacia L.), chestnut (C. sativa L.) and fir honeydew honey (Abies alba), respectively. Hexadecanoic acid has been reported in apple blossom (M. domestica) as well as in Mahaleb cherry (Prunus mahaleb), thus revealing similarity of both volatile profiles [23,40]. Stearic acid has been reported in Malaysian Tualang honeys (Koompassia excelsa)) by Syazana et al [41].…”
Section: Honey Markers For the Characterization Of Different Unifloramentioning
confidence: 98%
“…Moreover, in the same document, EFSA stated that exposure to coumarin exceeding the TDI by threefold for 1-2 weeks would not raise any safety concerns. The presence of coumarin in the leaves, fruits and seeds of P. mahaleb is known from the literature [12,51,52]. Because of the TDI set by EFSA, we quantified coumarin in mfce.…”
Section: Catechin Phenolic Acids and Coumarinmentioning
confidence: 99%
“…Benzaldehyde and lilac aldehydes are often found in various honey types. The latter were reported to occur abundantly and to be characteristic compounds of New Zealand nodding thistle honey [11], Greek citrus honey [12] and Croatian Prunus mahaleb L. honey [7]. Benzaldehyde is known to be responsible for the characteristic smell of bitter almonds where it is generated as a product of amygdalin hydrolysis [13] and plants from the genus Prunus are known to commonly contain cyanogenic glycosides, such as amygdalin.…”
mentioning
confidence: 99%